Neuropathic Changes of Osmicated Common Peroneal and Tibial Nerve in Diabetic Patients and the Related Risk Factors - Jamal Muhamad Ameen , Payman; Jawad Kathum, Talib; Baker , Hewa (Diyala Journal of Medicine, 2019)
So much studies done to present the diabetic neuropathic changes of the peripheral nerves but most of them were done experimentally on laboratory animals , but little about human diabetic neuropathic and structural changes specially of large nerves like common peroneal and tibial nerve .Accordingly the present work designed to study the neuropathic changes of the tibial and common peroneal nerve samples, taken from amputated legs of 30 diabetic patients (8 females and 22 males) at age ranging between (55-75) years, and from 30 cadavers (4 females and 26 males) at age ranging between (25-50) years as control group. The teased and osmicated tibial and common peroneal nerve fibers, and histological sections taken from diabetic patients showed different deformity and Morphometrical changes, of that ; paranodal swelling, segmental demyelination, some areas with an areas of un even myelin and shortest segmentation the (common peroneal nerve 22µ and tibial nerve 265µ ) in comparison to the control group. The multiple regression analysis, showed significant effect of age of the patient and duration of diabetes on the neuropathic changes.